1994
DOI: 10.1182/blood.v83.2.543.543
|View full text |Cite
|
Sign up to set email alerts
|

Activation of beta 1 integrin fibronectin receptors on HL60 cells after granulocytic differentiation

Abstract: Phorbol esters upregulate the functional affinity of beta 1 integrin receptors for fibronectin on human neutrophils and other leukocytes. We investigated the ability of phorbol myristate acetate (PMA) to stimulate the human promyelocytic cell line HL-60 to adhere to fibronectin, either in its undifferentiated state (HL60) or after dimethylsulfoxide-induced differentiation along the granulocytic pathway (dHL60). PMA stimulated little adherence of undifferentiated HL60 to fibronectin or to the 120-kD chymotrypti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This is particularly well documented for the platelet integrin o/iib/33 (34)(35)(36), fit integrins, such as VLA-6 (37,38), and 132 integrins, such as LFA-1 (39). Agonists which stimulate/31 integrin-mediated adhesiveness on hemopoietic and immune cells include activators of protein kinase C, such as PMA (9,40), cross-linking of antibodies specific for CD31 (24,41), the T cell receptor, CD7, CD28 (42), and certain activating anti-CD29 mAb (18,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 94%
“…This is particularly well documented for the platelet integrin o/iib/33 (34)(35)(36), fit integrins, such as VLA-6 (37,38), and 132 integrins, such as LFA-1 (39). Agonists which stimulate/31 integrin-mediated adhesiveness on hemopoietic and immune cells include activators of protein kinase C, such as PMA (9,40), cross-linking of antibodies specific for CD31 (24,41), the T cell receptor, CD7, CD28 (42), and certain activating anti-CD29 mAb (18,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 94%
“…For example, the absence of secondary granules will exclude a number of adhesion molecules as potential candidates in Mac-1-independent migration. 40 Mac-1 expression on DMSO-differentiated HL-60 cells has been well documented 26,[41][42][43] while Mac-1 expression on dbcAMP-differenti-ated HL-60 cells has not been well studied. Although some investigators have demonstrated positive staining for CD11b on dbcAMP-differentiated cells, the level of its expression did not differ from the level on undifferentiated HL-60 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additional adhesion pathways, including the α 5 integrin and the CD11/CD18 complex, could explain the observed residual adhesion of induced clone 15 cells to fibronectin. Indeed, we noted that the majority of induced cells expressed the α 5 integrin (56–58) concomitant with an upregulation of complement receptor type 3 (CR3 or CD11b/CD18).…”
Section: Discussionmentioning
confidence: 99%